1998
DOI: 10.1007/s11661-998-0216-9
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Al-3 Wt pct Mg matrix composites reinforced with Al2O3 and SiC particulates by the pressureless infiltration technique

Abstract: In Al-3 wt pct Mg/Al 2 O 3p (or SiC p ) composites fabricated by the pressureless infiltration method, the infiltration behavior of molten metal, the mechanical properties, and the interfacial reactions were investigated. The spontaneous infiltration of the molten Al-3 wt pct Mg alloy into the powder bed occurred at a relatively low temperature (700 ЊC for 1 hour under a nitrogen atmosphere). Spontaneous infiltration of the molten metal is related to the formation of Mg 3 N 2 by the reaction of Mg and nitrogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(29 citation statements)
references
References 34 publications
1
28
0
Order By: Relevance
“…[26] Others have suggested that N 2 plays a similar role in the production of aluminum composites, [27][28][29][30] although Clarke et al [31] showed that Mg vapor plays a key role. Magnesium has a higher vapor pressure than magnesium nitride, which suggests that the formation of the nitride phase may not be necessary for vapor transport to occur.…”
Section: Discussionmentioning
confidence: 99%
“…[26] Others have suggested that N 2 plays a similar role in the production of aluminum composites, [27][28][29][30] although Clarke et al [31] showed that Mg vapor plays a key role. Magnesium has a higher vapor pressure than magnesium nitride, which suggests that the formation of the nitride phase may not be necessary for vapor transport to occur.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the reinforcing components that give MMCs their excellent strength and wear characteristics also present unique challenges during machining operations. While great improvements have been shown in the production of near-net shape parts [2,3] there remains a pressing need for effective secondary processing. The primary difficulty when machining MMCs has * Corresponding author.…”
Section: Introductionmentioning
confidence: 99%
“…Matrices made from just aluminum do not fully wet the particles and therefore have relatively poor bonding compared to magnesium MMC or Al-Mg MMC. Lee et al [3] found that when machining MMCs bond failure of the reinforcement to matrix is one of the commonly observed defects in the finished part. Debonding either promotes breakout of the reinforcement or forms a crack from which fatigue cracks propagate in service.…”
Section: Introductionmentioning
confidence: 99%
“…It has been widely used to syntheses a variety of materials, such as amorphous alloys [2], nanocrystalline materials [3], intermetallic compounds [4] and so forth. Hexagonal boron nitride (h-BN), which exhibits comprehensive properties [5][6] of low density, excellent stability, high thermal conductivity, good lubricity and so on, is a promising reinforcement in aluminum metal matrix composites (AMMCs) for automotive and aerospace industrial applications [7]. In recent years, many researchers have paid much attention to the fabrication of AMMCs reinforced by BN, including by high-energy ball milling [8], pressureless infiltration [9][10] and other methods.…”
Section: Introductionmentioning
confidence: 99%